KONSEP PENGEMBANGAN DIRI ARISTOTELES - Esha, Muhammad In’am (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2004)
Self-actualization is one of the main ideas in the Aristotle’s ethic philosophy. According to Aristotle, man’s happiness depend on how much he could actualize his potencies through positive acts. There are two ways to actualize these potencies; theoretic and praxis. Theoretic actualization is human self-actualization through spiritual way, it means man’s actualization as zoon logon echon (the creature who has spirit). Praxis actualization is human potential expansion that is realized through participation in the social life, it means man’s actualization as zoon politicon (the social creature).The happy human is the human who has actualized his self-potencies both in theoretic and praxis. In Islamic term, that concept can be compared with the acknowledgment: “the perfect human (al-insan al-kamil) is the human who has been successful in his relation with God (vertical relation or habl min Allah) and his relation with other human or other creature (horizontal relation or habl min an-nas) Keyword: theoretic, praxis, and ethic.